2014
DOI: 10.1007/s12272-013-0315-z
|View full text |Cite
|
Sign up to set email alerts
|

Myriocin induces apoptotic lung cancer cell death via activation of DR4 pathway

Abstract: It has been known that myriocin inhibits melanoma growth. However, the effects and action mechanisms of myriocin on lung cancer cell growth have not been reported. In this study, we examined whether myriocin isolated from Mycelia sterilia inhibits cell growth of lung cancer cells (A549 and NCI-H460) as well as possible signaling pathways involved in cell growth inhibition. Different concentrations of myriocin inhibited the growth of lung cancer cells through the induction of apoptotic cell death. Consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…1), indicating that sphingolipid synthesis is required for estrous cycle cell proliferation (Baranda-Avila et al 2013). However, further studies are need to establish whether changes in cell metabolism and membrane properties, as a consequence of shingolipd depletion by myriocin, can induce apoptotic cell death leading to inhibition of cellular growth, in a similar manner as was previously reported in lung cancer cells (Choi et al 2014). Moreover, the use of many sphingolipidderived reagents has been described, and they are useful tools to further explore the molecular mechanisms involved in sphingolipid synthesis and homeostasis (Chen et al 1999).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…1), indicating that sphingolipid synthesis is required for estrous cycle cell proliferation (Baranda-Avila et al 2013). However, further studies are need to establish whether changes in cell metabolism and membrane properties, as a consequence of shingolipd depletion by myriocin, can induce apoptotic cell death leading to inhibition of cellular growth, in a similar manner as was previously reported in lung cancer cells (Choi et al 2014). Moreover, the use of many sphingolipidderived reagents has been described, and they are useful tools to further explore the molecular mechanisms involved in sphingolipid synthesis and homeostasis (Chen et al 1999).…”
Section: Discussionmentioning
confidence: 68%
“…Our results are in line with these observations, suggesting an important role for sphingolipids in cell cycle progression. Since sphingolipids are important mediators of both cellular proliferation and programmed cell death (Gangoiti et al 2008, Choi et al 2014, Li et al 2017, it is important to investigate the precise role of individual sphingolipid species on uterine epithelial cell proliferation. Inhibitors downstream of SPT must be used in order to determine distinct roles of each species (Canals et al 2011) and further elucidate the diverse pathways affecting uterine epithelial cell proliferation.…”
Section: Figurementioning
confidence: 99%
“…It was reported that numerous natural compounds showed anti-cancer effect via activation of DRs recently. In our previous study, we presented that BV suppressed cancer cell growth via activation of DR3 in NSCLC cells 10 , Myriocin induced apoptotic cell death through activation of DR4 in NSCLC cells 25 , (E)-2,4-bis (p-hydroxyphenyl)-2-butenal showed anti-cancer effect via activation of DR5 in NSCLC cells 12 . Our findings also showed that knock down of Fas or DR4 with siRNA partially abolished the inhibitory effect of PL on the NSCLC cell growth.…”
Section: Discussionmentioning
confidence: 93%
“…1 F. However, many necrotic cells with the triple addition of DL-PDMP plus D-NMAPPD plus myriocin were detected compared with the dual addition of DL-PDMP plus D-NMAPPD (data not shown). It was stipulated that the triple addition caused synergistical cell death by the combination of myriocin and anti-tumor drugs (DL-PDMP plus D-NMAPPD) against A549 cells as described previously [15] .…”
Section: Resultsmentioning
confidence: 99%